Novel Coumarin–β-Thio Carbonyl Derivatives with Potent Antioxidant Activity - Abdulhussein, Ali Mohammed; Raheem, Leaqaa Abdulredha; Suwaid, Maan Abdul-Razzaq (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Antioxidants play a key role in mitigating oxidative stress–related disorders, driving interest in developing synthetic molecules with strong radical-scavenging capacity. Specific Background: Coumarin-based scaffolds exhibit diverse biological activities, yet limited studies have explored their β-thio carbonyl hybrids as potential antioxidant agents. Knowledge Gap: Despite the therapeutic promise of coumarin hybrids, their structure–activity relationships and antioxidant effectiveness remain underexplored. Aim: This study synthesized and characterized five novel coumarin–β-thio carbonyl derivatives and assessed their antioxidant potential using the DPPH assay. Results: Structural confirmation was achieved through ¹H-NMR, ¹³C-NMR, and mass spectrometry, verifying the successful formation of all compounds. Notably, compound 11 displayed the strongest radical-scavenging capacity (IC₅₀ = 17.89 μM), surpassing ascorbic acid (IC₅₀ = 23.04 μM). Novelty: This work provides the first comprehensive structural and biological evaluation of a new series of coumarin–β-thio carbonyl hybrids featuring various electron-donating and electron-withdrawing substituents. Implications: The findings highlight these derivatives, particularly dimethylamino-substituted analogues, as promising candidates for further development in antioxidant-based therapeutic applications.Highlights: Five new coumarin–β-thio carbonyl derivatives were successfully synthesized and validated. Compound 11 exhibited the strongest radical-scavenging activity among all tested molecules. Electron-donating substituents improved antioxidant performance. Keywords: Coumarin Derivatives, β-Thio Carbonyl, Antioxidant Activity, DPPH Assay, Heterocyclic Synthesis